(untitled) (Balneo and PRM Research Journal, 2022)
(1) Background: The purpose of the study was to analyze the effect of two different training modes towards the development of body composition, aerobic and anaerobic endurance of female handball players aged 18-23, in COVID-19 pandemic. (2) Methods: 18 female handball players from the second division were divided into two groups: Group 1 subjected to Tabata Program (n=9) and Group 2 trained using HIIT Program (n=9). (3) Results: Paired Sample T-Test was carried in the statistical analysis and the significance level was determined (p < .005). The group subjected to HIIT training achieved greater increases in endurance performance than the group carrying out Tabata training (p < .005). (4) Conclusions: Different results were obtained when studying changes regarding segmental analysis of upper, lower limbs and trunk. Both groups undergoing Tabata and HIIT training registered improvements.